The Addition Extract of Red Dragon Fruit (Hylocereus polyrhizus) Kefir and Aging Time on Ice Cream Made of Goat Milk - Najiah Ahmad; Edhy Mirwandhono; Armyn Hakim Daulay; Tri Hesti Wahyuni; Hamdan . (Jurnal Peternakan Integratif, 2018)
Abstract. There is few people who like goat milk, that is why process of making goat milk into ice cream is needed. Therefore, a research has been done at Animal Production Laboratory of Husbandry Department, Faculty of Agriculture, University of North Sumatera, from April to May 2018. The design which used in this research is Randomized block design (RAK) with two factors: kefir concentration (P): (0%, 10%, 20%, 30%) and aging time (L): (6, 12, 18, 24 hours). Parameters which observed were overrun, melting time and organoleptic test (color, aroma, texture, taste).The results showed that the interaction between kefir concentration and aging time gave a significant effect to organoleptic result of flavor and did not give significant effect to overrun, melting time and organoleptic results (color, texture, taste). The concentration of  kefir had given significant effect to melting time and organoleptic results (color, aroma, texture, taste) and did not give significant effect to overrun result. The aging time gave a significant effect to overrun, melting time and organoleptic results (color, aroma, texture), and did not give a significant effect on organoleptic taste result. The best result was obtained in addition of kefir extract of red dragon fruit 30% with aging time aged 6 hours on ice cream made of goat milk.